The design and optimisation of cross layer routing and medium access control (MAC) protocols in cognitive radio networks - Madiba, Miyelani Silence (University of Limpopo, 2021)
Cognitive Radio (CR) is a promising technology designed to solve many issues, especially spectrum underutilisation and scarcity. The requirement for spectrum effectiveness was essential, and consequently, the possibility of CR arrived along and introduced the unlicensed Secondary Users (SU). SU can operate on the unlicensed and licensed spectrum bands on a condition that they avoid interference with the licensed Primary Users (PU). This approach is called the Dynamic Spectrum Allocation (DSA) and has solved the underutilisation of spectrum using the spectrum holes. The United States of America’s telecommunication regulator Federal Communication Commission (FCC) introduces spectrum bands by unlicensed users looking at the rapid growth of wireless applications and devices; therefore, the Fixed Spectrum Allocation (FSA) become inadequate because of the spectrum crowded issues. Accomplishing this design requirement while meeting the Quality of Service (QoS) of SU is a challenge; thus, the cross-layer design (CLD) was introduced to enhance the efficiency and effectiveness of Cognitive Network (CN). CLD arrangements in Cognitive Radio Network (CRN) are empowering; however, there are yet numerous issues and difficulties that must be addressed, such as resource allocation and others that may negatively impact network performance. Routing in CRN also necessitates the cross-layering approach. Therefore, in this work, designing a protocol that will solve routing issues and channel selection will also maximise spectrum opportunistically. In this study, we propose the Optimised Cognitive Cross-layer Multipath Probabilistic Routing (OCCMPR) protocol, which is the optimised version of Cognitive Cross-layer Multipath Probabilistic Routing (CCMPR). We used MATLAB simulation installed in the Windows 10 operating system (OS) tool to generate comparison results. We compared the OCCMPR protocol with the existing protocols, the Cognitive Ad-hoc On-demand Distance Vector (CAODV) and the CCMPR protocols.
Thesis (M.Sc.) -- University of Limpopo, 2021
Keywords: Cognitive Radio; Technology; Wireless communication systems; Cognitive radio networks; Signal processing; Speech processing systems; Image processing; Communication in engineering